The Role of the Whistle-Blowing System in Relation to Other Objection making Systems in Japan - Akio, Kamiko (Indonesian Association for Public Administration, 2025)
Whistleblowing systems in local Japanese governments represent a relatively new addition to the country's administrative framework. Originally designed as a general system applicable to both public and private sectors, these systems were later adapted for local governments with minimal adjustments. This has led to ambiguity in distinguishing whistleblowing from other established objection-making systems such as those managed by personnel commissions and equity missions. Drawing on the author's experience as the chairman of a whistleblowing committee in Fukuchiyama City, this study explores the challenges of demarcating whistleblowing from other objection channels, particularly in cases involving staff remuneration, incompetent officials, and workplace harassment. The study employs a qualitative approach, analyzing real-world cases and reviewing legal frameworks, including the Local Public Personnel Act and local bylaws. This highlights the lack of standardization of whistleblowing systems across Japanese municipalities, as each local government designs its own system within vague central guidelines. This research identifies instances where whistleblowing is used inappropriately, bypassing more specialized systems, and examines the implications of this trend. It also considers the reasons for the popularity of whistleblowing, such as the allowance for anonymous reporting and the simplicity of the process, and suggests that whistleblowing systems have expanded the scope of objection-making in Japanese local governments; they have also created confusion by overlapping with existing systems. The paper concludes with recommendations for a clearer demarcation between whistleblowing and other objection channels, emphasizing the need for better-defined roles and expertise in handling different types of complaints. This study contributes to the broader discourse on whistleblowing systems and their integration into public administration.